1983
DOI: 10.1111/j.1471-0528.1983.tb06743.x
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast alterations in the placental bed in relation to physiological changes in spiral arteries

Abstract: Summary. Ninety‐three placental bed biopsies containing a segment of a spiral artery at the level of the decidual–myometrial junction (53 with and 40 without physiological changes) were histologically investigated for depth of trophoblastic penetration of the uterine wall, formation of trophoblastic multinucleated giant cells and the enzyme histochemical characteristics of the interstitial (stromal) and vascular (intramural) trophoblast. The depth of trophoblastic penetration was not related to the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
4

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 12 publications
1
15
0
4
Order By: Relevance
“…Although we are still ignorant about the specific role of mononuclear and multinuclear trophoblasts in the placental bed [18], one of the functions of the extravillous trophoblast (EVT) can be to tolerate hypoxia for successful invasion to occur, whereas other functions may include transformation of the maternal spiral arteries, adherence to and digestion of the extracellular matrix, and interaction with the maternal immune system [19]. Some authors believe that MTGC form because of disturbed migration into the arterial wall, and as a result, prevalence of MTGC is increased in pregnancies in which vascular physiologic changes are lacking [20]. Regulation of human trophoblast migration and invasiveness is complicated and involves many stimulating and inhibiting factors [21,22] that will not be discussed here in detail.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although we are still ignorant about the specific role of mononuclear and multinuclear trophoblasts in the placental bed [18], one of the functions of the extravillous trophoblast (EVT) can be to tolerate hypoxia for successful invasion to occur, whereas other functions may include transformation of the maternal spiral arteries, adherence to and digestion of the extracellular matrix, and interaction with the maternal immune system [19]. Some authors believe that MTGC form because of disturbed migration into the arterial wall, and as a result, prevalence of MTGC is increased in pregnancies in which vascular physiologic changes are lacking [20]. Regulation of human trophoblast migration and invasiveness is complicated and involves many stimulating and inhibiting factors [21,22] that will not be discussed here in detail.…”
Section: Discussionmentioning
confidence: 98%
“…The findings are in keeping with the observation that, in absence of vascular physiologic changes at the level of decidual-myometrial junction, a significant accumulation of MTGC was found before 36 weeks of gestation. Beyond 36 weeks, whether physiologic changes are present or not, there were only small numbers of MTGC [20]. The increase of extravillous trophoblast in the same conditions as MTGC (Table 1) [31], mutual correlation of those 2 lesions, and similar gestational age profile (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Based on numerous reports describing changes in blood pressure (BP), heart rate (HR), and other hemodynamic variables throughout pregnancy, there has been a general agreement that BP drops in mid-trimester, followed by a progressive increase until term [1][2][3][4][5][6][7][8]. This mid-trimester drop in BP has in part been explained in terms of the development of the low-resistance uteroplacental vascular system [9][10][11] and modification of the renin-angiotensin-aldosterone system [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Foram incluídas gestantes com feto único e vivo, com idade gestacional igual ou superior a 28 semanas e placenta normalmente inserida. Foram excluídas pacientes que apresentaram: descolamento prematuro da placenta, acretismo placentário, malformações fetais, diabete melito, infecções agudas ou crônicas, colagenose, antecedentes de doenças tromboembólicas, tabagismo, pré-eclâmpsia sobreposta, aloimunização pelo fator RH, alcoolismo, nefropatias e fragmentos teciduais do leito placentário que não preencheram os critérios de validação da amostra após avaliação histopatológica 1,18,19 ESTUDO DA MORFOLOGIA VASCULAR DO LEITO PLACENTÁRIO NA HIPERTENSÃO ARTERIAL CRÔNICA Alterações hiperplásicas das camadas íntima e média: definidas pelo espessamento da camada íntima e da camada média (Figura 1d). Necrose caracterizada pela perda celular e eosinofilia intensa de todas as camadas (Figura 1e).…”
Section: Introductionunclassified